Astaxanthin Production from Green Microalga Haematococcus pluvialis under Various Bean Sprout Media Concentrations and Duration of UV Radiations - Hary, Biaggi Rakhmat Rheinan; Sidharta, Boy Rahardjo; Arsiningtyas, Ines Septi (Journal of Tropical Biodiversity and Biotechnology, 2024)
Astaxanthin (AX) is known as a very strong antioxidant and has been utilised in many kinds of products such as foods, pharmaceutical, cosmetics, aquaculture, etc. One of the natural resources of AX is Haematococcus pluvialis which has been investigated by some researchers in order to enhance the AX production. However, the production of AX from the microalgae is still costly, hence, this present research is proposing low-cost methods namely bean sprout media (BSM) as an alternative growth media and UV radiation. The variations of BSM concentrations (2, 4, and 6 %) and times of UV radiation (1.5 and 3 hrs) were treated to H. pluvialis in laboratory conditions. BSM 4 % treatment showed an optimum growth of the microalga at 427 x 104 cell/ml (day 8) which also exhibited macrozooid, palmella, and aplanosore phases. UV radiation for 3 hr revealed that the concentration of AX production was as much as 17.37±0.04 mg/l. The research results were potential to be developed further in order to discover better and cheaper methods for scaling up AX production.